DESIGNING A DIDACTICAL SITUATION ON SYMBOL SENSE OF MINUS SIGN IN LEARNING ARITHMETIC OPERATION OF INTEGER - FUADIAH, NYIAYU FAHRIZA (Sriwijaya University Learning and Education International Conference, 2016)
Mathematics textbooks are usually a reference for teachers to convey the material inclass. The existence of textbooks help teachers to facilitate the learning processbecause their contain some descriptions of concepts, example problems, andevaluations so that the concepts and flow of thought contained in the textbook canguide teachers in the learning process. The study on mathematics textbooks ofprimary and junior high school on the material negative numbers less meaning thesymbol of minus sign (symbol sense of minus sign) beforehand as the initial conceptof negative numbers so that students do not understand the meaning of negativenumbers at the next level. The learning process is more likely to emphasize theprocedure only that resulting in a leap of information and thinking experienced bystudents. Finally, character of studentâs thinking forced to jump from the concreteinto abstract thinking. Based on the results of a study conducted by researcher on thestudents of seventh grade, the concept of negative numbers became an obstacle inperforming arithmetic operations of numbers. In integers which there are negativeintegers in shows that most of them do not understand the meaning of the symbolminus sign as a prerequisite to understanding arithmetic operations involvingnegative integers. Therefore, teachers need to design a learning through a didacticalsituation on symbol sense of minus sign which appropriate to the character of thestudents thinking.